2023
DOI: 10.1007/s11468-023-01874-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Titanium Dioxide and MXene Nanomaterial-Based Surface Plasmon Resonance Biosensor for Virus SARS-CoV-2 Detection

Abstract: A novel surface plasmon resonance-based biosensor for SARS-CoV-2 virus is proposed in this article. The biosensor is a Kretschmann configuration-based structure that consists of CaF 2 prism as base, at which silver (Ag), TiO 2 , and MXene nanolayers are used to enhance the performance. Theoretically, the performance parameters have been investigated by means of Fresnel equations and transfer matrix method (TMM). The TiO 2 nanolayer not only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The SPR biosensor under consideration has the potential to facilitate precise detection of the SARS-CoV-2 virus in its early stages, hence aiding in the timely identification of COVID-19 patients. 349 Recent research demonstrated the remarkable sensitivity of MXenes, Nb 2 C, and Ta 2 C in the context of SERS for virus identification. The substrates exhibit noteworthy SERS enhancement, which is accomplished through charge transfer resonance enhancement and electromagnetic enhancement.…”
Section: Mxene-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPR biosensor under consideration has the potential to facilitate precise detection of the SARS-CoV-2 virus in its early stages, hence aiding in the timely identification of COVID-19 patients. 349 Recent research demonstrated the remarkable sensitivity of MXenes, Nb 2 C, and Ta 2 C in the context of SERS for virus identification. The substrates exhibit noteworthy SERS enhancement, which is accomplished through charge transfer resonance enhancement and electromagnetic enhancement.…”
Section: Mxene-based Biosensorsmentioning
confidence: 99%
“…The SPR biosensor under consideration has the potential to facilitate precise detection of the SARS-CoV-2 virus in its early stages, hence aiding in the timely identification of COVID-19 patients. 349…”
Section: E2dnms-based Poc Biosensors For Sars-cov-2 Detectionmentioning
confidence: 99%
“…The refractive index of the CaF 2 prism is as [5,7], Here, refractive index of BaTiO 3 is 2.404 [6]. Also, transition metal dichalcogenides WS 2 layer is used.…”
Section: Numerical Modeling Of Proposed Sensormentioning
confidence: 99%
“…FWHM represents the full width at half maximum of the SPR curve, a dimensionless parameter. The quality factor (Q) is de ned as the ratio of sensitivity (S) to the FWHM of the re ectance curve [5].…”
Section: S = (8)mentioning
confidence: 99%
See 1 more Smart Citation